2010
DOI: 10.1021/tx100242w
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Modifications of Hemoglobin by Nitrite Anion: Formation Kinetics and Properties of Nitrihemoglobin

Abstract: The green nitrihemoglobin (α2β2 tetramer, NHb) was prepared by the aerobic reaction of excess nitrite with human hemoglobin A0 under mildly acidic conditions. A rate equation was determined and found to depend on nitrite, hydrogen ion and oxygen concentrations: –d[HbNO2]/dt = (k1 + k2(Ka[HNO2])[O2]1/2)•[ HbNO2], where k1 = 2.4 (±0.9) × 10-4 s-1, k2 = 1 (±0.2) × 105 M-5/2s-1 and Ka is the acid dissociation constant for nitrous acid (4.5 × 10-4 M). Also, the chemical properties of NHb are compared to those of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 40 publications
3
29
1
Order By: Relevance
“…The possibility that the nitrated heme originated by a substitution of a proton by NO 2 on a vinyl group was suggested by previous work on nitriMb (33) and nitriHb (34,35). These green Mb and Hb derivatives contain a 2-nitrovinyl group and are generated in vitro by exposing the proteins to excess NO 2 − .…”
Section: Purification and Identification Of Lb Components And Modifiementioning
confidence: 99%
“…The possibility that the nitrated heme originated by a substitution of a proton by NO 2 on a vinyl group was suggested by previous work on nitriMb (33) and nitriHb (34,35). These green Mb and Hb derivatives contain a 2-nitrovinyl group and are generated in vitro by exposing the proteins to excess NO 2 − .…”
Section: Purification and Identification Of Lb Components And Modifiementioning
confidence: 99%
“…It is important that in the absence of methylglyoxal neither GSNO nor nitrite provoked metHb conversion to nitriHb. It was earlier shown that green nitriHb form appeared as result of metHb interacting with nitrite in aerobic conditions [30,31]. Otsuka et al [31] supposed that metHb was modified by nitrite complex with heme iron and nitration reagents such as N 2 O 3 and N 2 O 5 .…”
Section: Resultsmentioning
confidence: 99%
“…The amount of reduced Hb was determined through oxyHb (ε 576 = 14.6/mM/cm), formed in cuvette for spectrophotometric measurements in aerobic conditions. Formation of nitriHb was determined using an absorbance band of reduced hemochromogen (582 nm) in alkaline pyridine solution (30% pyridine solution in 0.1 M NaOH) [31].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations